Factors Related to Dietary Arrangements of Diabetic Mellitus Patients - Kurniawati, Trina; Budiarto, Eka; Kusuma, Nur Intan (Ahmar Metastasis Health Journal, 2024)
Dietary management of patients with diabetes mellitus needs special attention because it can have a direct impact on the instability of blood sugar levels. There are factors that affect the patient's ability to manage their diet. The purpose of this study was to determine sociopsychodemographic factors and the relationship with dietary management of patients with diabetes mellitus.  This research is a descriptive correlative study with a cross-sectional approach. The sample used was purposive sampling. The research was conducted by giving questionnaires to respondents. The questionnaires used were a characteristic questionnaire, Self Reporting Questionare (SRQ) 20, and Food Frequency Questionare (FFQ). The data from the study were analyzed using logistic regression. The results obtained factors associated with dietary management of DM patients include occupational factors and economic status with a p-value of 0.021 and 0.042 respectively. Other factors including age, gender, education, culture, and anxiety are not associated with dietary management of DM patients (p-value 0.185; 0.855). Dietary arrangements of DM patients obtained most patients have done DM diet in accordance with the recommendations. Sociopsychodemographic factors associated with dietary management of DM patients are employment and economic status. Employment factors and economic status are modifiable factors so these factors become reinforcements for patients in managing the diet of DM patients.